2006
DOI: 10.1080/03235400500094084
|View full text |Cite
|
Sign up to set email alerts
|

Studies on insecticidal potential of extracts ofGmelina arboreaL. products for insect pests control on cowpea. 1. The legume flower bud thrips,Megalurothrips sjostedtiTrybom

Abstract: The effects of weekly foliar application of extracts of Gmelina arborea (L.) fruits, bark and leaves on flower bud thrips, Megalurothrips sjostedti Trybom and the pod carrying capacity of cowpea variety SAMPEA 7, were investigated in field studies in the 1998 and 1999 cropping seasons. All the Gmelina extracts and the synthetic insecticide (Uppercott) caused significant a reduction of thrips on treated plots compared to the untreated check. However, no significant differences were observed on the number of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…who reported highest pod damage in untreated plots with extracts of West Africa black pepper, African pepper, alligator pepper, ginger and chill pepper increased grain yield and pod density are also attributed to the reduced pod damage by chilli pepper extract. This supports the work ofOparaeke et al, (2005) who reported higher pod density in plot treated with…”
supporting
confidence: 92%
See 1 more Smart Citation
“…who reported highest pod damage in untreated plots with extracts of West Africa black pepper, African pepper, alligator pepper, ginger and chill pepper increased grain yield and pod density are also attributed to the reduced pod damage by chilli pepper extract. This supports the work ofOparaeke et al, (2005) who reported higher pod density in plot treated with…”
supporting
confidence: 92%
“…It is against this background and coupled with the need to add to the present status of knowledge in the bioefficacy of plant extracts that this study was initiated to assess the effect of chilli pepper (Capsicum frutescens L.) intercropping and its bioefficacy on the performance and insect pest management of Bambara groundnut (Vigna subterranean (L.) Verdc. (2022a( ), Amatobi (2000 and Oparaeke (2005).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory effect of methanol extract of G. arborea and its fractions can be attributed to the presence of the flavonoid [8] present therein. Moreover, the insecticidal activity of G. arborea extracts against Megalurothrips sjostedti [9] and Callosobruchus chinensis and Sitophilus oryzae [10], would healing effects [11], anti-ulcer potentials [12] and antiangiogenic activity [13] have been reported. It was also reported that an ethanolic leaf extract of G. arborea has potent in vitro cytotoxic activity against colon cancer (COLO 201), gastric cancer (HT-29) and human oesophagel cancer (TE-2) cell lines [14].…”
Section: Introductionmentioning
confidence: 99%